IMPLEMENTASI PENDEKATAN UNDERSTANDING BY DESIGN (UBD) DALAM PEMBELAJARAN IPAS KELAS V SEKOLAH DASAR - Lisa Kurnia Wardani; Dwi Anggraeni Siwi (STKIP Subang, 2026)
This study aims to describe the implementation of the Understanding by Design (UbD) approach in IPAS (Natural and Social Science) learning in Grade V Elementary School and to identify the obstacles encountered. This research uses a qualitative descriptive methode conducted at SD Negeri Gentan 03, Sukoharjo Regency. Data collection was carried out through observation, interviews, and documentation. Data validity was ensured through source triangulation and method triangulation. The result show that the implementation of UbD in IPAS learning has been carried out well through three systematic stages: (1) formulating learning objectives (desired results) that focus on higher-order thingking skills and meaningfull understanding; (2) determining evidence of assessment (determine acceptable evidence) through diagnostic, formative, and summative assessments as well as authentic assessment through project-based activities; and (3) planning learning experiences (plan learning experiences and instruction) using the Problem Based Learning (PBL) model integrated with technology media, group discussion, presentation, and reflection. The main obstacle found is time limitations in designing detailed and structured learning plans. However, this obstacle can be overcome by managing time effectively and allocating a special day for UbD-based learning planning.